Detection of the frequency of microbial defilement "in-use" soap products at various dental departments: A microbiological research - Rohan Sachdev; Kriti Garg; Shubhra Saxena; Samiksha Shwetam; Vishal Mehrotra; Akash Srivastava (Wolters Kluwer Medknow Publications, 2020)
Context: Hand washing by a dental health professional before having contact with a patient's oral cavity is considered a fundamental dental clinic infection control measure. Aims: The aim of this study was to evaluate bar soap and liquid soap from dental departments for microbial contamination while it was in use. Settings and Design: This exploratory, cross-sectional study was carried out to identify microorganisms' presence in handwashing with liquid and bar soap at clinical and nonclinical departments in a dental college. Subjects and Methods: In the 2-month study period, all the dental students, dental faculty, and the other auxiliaries present were the participants, and a total of 35 handwashing place samples from 15 different dental departments were collected. The test tube samples of bar soap and liquid soap were all transferred to the microbiology laboratory for microbiological analysis of the samples. Statistical Analysis Used: Data were analyzed using a one-sample paired t-test and independent Student's t-test. Results: Nine different microbial species were identified. In both soaps, the abundance of Staphylococcus aureus was higher as compared to that of other microorganisms. Further, in both soaps, the mean number of microorganisms increased statistically significantly (P < 0.05 or P < 0.01 or P < 0.001) at post-use as compared to at pre-use except Aspergillus niger in liquid soap. However, the post-use mean abundance of microorganisms was found similar (P > 0.05) between the two groups (soaps). Conclusions: The microbial load of the in-use bar soap and liquid soap constituted a mixed flora of Gram-positive bacteria, Gram-negative bacteria, aerobes, anaerobes, and fungi. The results indicate that the bar soap under "in-use" condition harbors more of microorganisms as compared to that of liquid soap, and handwashing with such a soap may lead to the spread of infection.